Produksi dalam Pandangan Islam (Studi Kasus: UMKM Keripik Pisang Mas Kiki) - Chintya Pradilla Putri; Yuda Mahendra Hasibuan (Yayasan Literasi Sains Indonesia, 2023)
One industry that has a strong impact on Indonesia's economic growth is Micro, Small and Medium Enterprises (UMKM). Micro, Small and Medium Enterprises (UMKM) are productive business entities that are independent in all economic sectors. Micro businesses are defined as people or business entities that sell goods and services directly to end consumers to meet their needs. One of the UMKM activities in the business sector is located on Jl. Marendal Gg. Sipar City of Medan has a snack industry called Keripik Pisang Mas Kiki. As a branch of the economy based on the availability of natural raw materials, according to an Islamic economic perspective, entrepreneurs must participate in preserving the environment to maintain the availability of raw materials in nature. Based on this, the objectives of this study are: first, how to apply the factors of production in the Mas Kiki banana chip industry and secondly, how to identify production factors in the Mas Kiki banana chip industry in an Islamic perspective. This research uses a qualitative approach with a descriptive type.